Methacrylated lignosulfonate as compatibilizer for flax fiber reinforced biocomposites with soybean-derived polyester matrix. (December 2020) - Xu, Yunsheng; Adekunle, Kayode; Ramamoorthy, Sunil Kumar; Skrifvars, Mikael; Hakkarainen, Minna
Abstract: The poor adhesion between natural fibers and polymer matrix restricts the mechanical performance of natural fiber reinforced composites. Here, lignosulfonate was methacrylated and evaluated as a potential compatibilizer for flax fiber reinforced soybean-derived polyester thermosets. Significant improvement in both tensile and flexural properties of the fiber composites were achieved when the flax fiber mat was treated with methacrylated lignosulfonate solution. In particular, the flexural modulus and flexural strength more than doubled from 2.6 to 6.7 GPa and from 36 MPa to 76.8 MPa, respectively when the fibers were soaked in 5 wt % MLS solution. The SEM analysis revealed improved fiber-matrix interface and lower extent of fiber pull-out in the methacrylated lignosulfonate treated fiber composites, which correlates with the improved mechanical properties. Highlights: Methacrylated lignosulfonate effectively compatibilized natural fiber reinforced thermosets. Significant improvement in flexural and tensile strength were achieved. Smoother fracture surface and less fiber pull-out after treatment with methacrylated lignosulfonate.